2014
DOI: 10.1007/s10965-014-0584-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of micro-molded exfoliated clay nanocomposites by means of ultrasonic technology

Abstract: Ultrasound micro-molding technology has been tested as a new method to get polymer/clay nanocomposites. Biodegradable polylactide (PLA) and poly (nona-methylene azelate) (PE99) have been used as polymer matrices, whereas different silicate clays have been assayed. The new technology is able to get specimens without evidences of degradation during processing. Only the use of organo-modified clays could give rise to a slight molecular weight decrease when the poly (alkylene dicarboxylate) sample was considered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
10
0
2
Order By: Relevance
“…Interestingly the T cc values are slightly enhanced with respect to that of PLA matrix, contrary to data generally obtained (showing a decrease of T cc ) and invoking nucleation effects [23] mainly due to intercalated morphologies. Stronger interactions and consequently exfoliated morphologies accounted for a different behaviour, as here observed, and resulting in a delayed crystallization [24,25]. After annealing the T g values increased as result of increased amorphous rigid fraction owing to raised crystallinity.…”
Section: Resultssupporting
confidence: 55%
“…Interestingly the T cc values are slightly enhanced with respect to that of PLA matrix, contrary to data generally obtained (showing a decrease of T cc ) and invoking nucleation effects [23] mainly due to intercalated morphologies. Stronger interactions and consequently exfoliated morphologies accounted for a different behaviour, as here observed, and resulting in a delayed crystallization [24,25]. After annealing the T g values increased as result of increased amorphous rigid fraction owing to raised crystallinity.…”
Section: Resultssupporting
confidence: 55%
“…PE99 samples could be processed under relatively mild conditions, as previously established [15]. Thus, a minimum irradiation time of 1.2 s, low amplitude of 24 μm, and a moderate molding force of 300 N were sufficient to guarantee a 100% molding efficiency.…”
Section: Dispersion Of Functionalized Silica Micro-and Nanoparticles mentioning
confidence: 89%
“…Therefore, optimization of processing parameters to obtain minimally degraded samples is an essential step in applying the new micro-molding technology. In this sense, we have recently found that it is possible to establish appropriate conditions for biodegradable polymers that could be interesting for the production of biomedical devices such as polylactide (PLA) [13], poly(butylene succinate) (PBS) [14], and poly(nonamethylene azelate) (PE99) [15]. Degradation logically increases with irradiation time and amplitude, but a minimum period is necessary to ensure complete injection into the mold, as well as a minimum amount of vibration energy.…”
Section: Introductionmentioning
confidence: 99%
“…Uma possível explicação seria que as moléculas do glicerol se intercalaram entre as camadas da MMT evitando a interação entre a matriz polimérica e a MMT. Por outro lado, na curva B, que representa a menor concentração de MMT estudada, o pico teve uma leve diminuição que pode ser explicada por uma possível esfoliação das nanopartículas de MMT devido à baixa concentração da argila e pela inclusão de cadeias poliméricas entre as camadas das nanopartículas (DÍAZ et al, 2014;GÜNISTER et al, 2007).…”
Section: Propriedades Estruturais Dos Filmesunclassified
“…Além disso, o pico de difração em 2θ = 10,2° refere-se a um alto grau de desacetilação da quitosana (≥ 85 %). Por outro lado, os reforçadores tais como a MMT mostraram o pico característico em 2θ = 7,2° o qual corresponde a um espaçamento entre as camadas lamelares de 12,6 Å (d001) (DÍAZ et al, 2014). E as fibras de bambu exibiram picos a 2θ = 22,0° e dois picos de difração sobrepostos a 2θ = 15,7° e 17,7°, respectivamente, os quais podem ser atribuídos à estrutura polimórfica da celulose I ou celulose nativa (CHANG et al, 2010;LU et al, 2014).…”
Section: Propriedades Estruturaisunclassified